Analysing the working process between designer and carpenters in the furniture industry at Batu Pahat, Johor, Malaysia - Afendi, Nurul Fadilah Azwanie (2022)
The collaboration between designers and carpenters in furniture industries at Batu Pahat, Johor need to be improve in order to have a good quality of work during manufacturing process. From the researcher working experience as designer in furniture company at Batu Pahat, Johor, there is a need to study the working process understanding between designers and carpenter to improve design collaboration technique during manufacturing process. Each of designer and carpenter need to know their own task to maintain their quality of work during manufacturing process. The purpose of this study is to analyse the working process between designer and carpenter in the furniture industries. This analysis is to improving the design collaboration between designer and carpenter. This study adopted a mixed- method approach. The first Delphi approach is applied in this study because it only used a few designer and carpenter from the two furniture company at Batu Pahat, Johor. The qualitative approach that applying observation and case study method is to analyse the design process that use during manufacturing process. This study revealed the differentiation of design process between designer and carpenter. This study developed a list of design process that adopted from furniture design process for a guidance to designer and carpenter during manufacturing process. A product data form(PDF) was develop by adopting Bill Of Material (BOM). The furniture company will used this PDF for saving their product data in order. This PDF also used as a guidance to designer in order understand carpenter language easily. It can be summarized that the list of design process is needed in furniture company. This design process will used as a guidance to have a better understanding of working task for each designer and carpenter. The PDF contributes to the furniture company as a standard guidance for the designer to understand carpenter language in the future.